Sinergi Mahasiswa Dan Masyarakat Parparean II Dalam Mewujudkan Lingkungan Sehat - Merdiani Gulo; Parsaoran Silalahi; Alfredo Butarbutar; Imanuel R. Hutagalung; Farans Purba; Restu Sihombing (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service activity is related to the role of students in setting an example for society in creating a clean and healthy environment. This activity is a platform that allows students to directly contribute to addressing issues in the community. This activity aims to raise public awareness about a clean and healthy environment. The methods used in this program include discussions and coordination with village officials, field activities such as community service, the creation of bamboo waste banks, and socialization. The result of this activity is that the students gained direct experience with social issues, implemented solutions, and increased the community's awareness of cleanliness and environmental health.